21 SOCIAL AND COMMUNITY SUPPORT ASSOCIATED WITH BARRIERS TO CARE AND DISEASE SEVERITY IN PEDIATRIC INFLAMMATORY BOWEL DISEASE AT DIAGNOSIS. (7th February 2019) - Dotson, Jennifer L; Bricker, Josh; Crandall, Wallace; Chisolm, Deena; Mackner, Laura
Abstract: Background: Little is known about health system barriers from the patient and family perspectives in children with inflammatory bowel disease (IBD), or potential targets for solutions. In our previous work, families primarily identified psychosocial barriers to care at diagnosis, suggesting that social and community support may be a promising avenue for intervention. In fact, social (from family and friends) and community support have been associated with improved outcomes in children with other chronic conditions. Our aim was to investigate relationships between barriers to care, social and community support, and disease severity in a prospective cohort of newly diagnosed children with IBD and their caregivers. Methods: This study is a prospective longitudinal assessment of 85 newly diagnosed IBD patients and their caregivers. The inclusion criteria were: age 2-18, <3 months from diagnosis, and English literacy. Patients ≥ age 11 and caregivers completed electronic questionnaires with Likert-scale on health system barriers, social support (Multidimensional Scale of Perceived Social Support; MSPSS) and community support (Perceived Community Support Questionnaire; PCSQ). PCSQ assesses 3 dimensions of community support: social integration, participation, and use of community organizations. Disease severity was assessed via Physician Global Assessment (PGA) during a routine clinic visit. Relationships between number of barriers, MSPSS and PCSQ scores, and PGA scores were evaluated using Pearson correlations. Results: Available data on subjects included 79 patients, 84 primary caregivers (89% female), and 28 secondary caregivers. The patients were 47% female, mean age 13.4 ± 3.6 years, 82% white race. 72% of primary caregivers were married, 63% employed full-time, median family size 4, median income 70, 000-79, 999. Most patients had Crohn's disease (72%) and mild disease severity (61% based on PGA). Types of barriers identified were psychosocial, financial, school, treatment, and transportation. Greater community support was associated with fewer psychosocial barriers for both parents and patients. More social support was associated with fewer psychosocial barriers for patients only. None of the other types of barriers, nor total number of barriers were associated with community or social support. Parents reporting better community and social support had children with less severe disease. Conclusion: Social and community support may be associated with fewer health system barriers as well as better health outcomes at diagnosis. This suggests that social and community support may be important targets for improving both access to care and health outcomes.